Advances in Osseointegration for Dental Implants: Influencing Factors and Measuring Methods - Antal, Mark Adam; Novák, Péter (Archive of Orofacial Data Science, 2025)
AIM: To review the latest research data on osseointegration and understand influencing factors as well as measurement methods associated with osseointegration. METHODS: A literature review was conducted using the PubMed and ScienceDirect databases, identifying and classifying articles from the last 15 years based on quality and relevance. RESULTS: Dental implantology has advanced significantly since its inception 60-70 years ago. Current research showcases diverse methodologies and examines various aspects of osseointegration. While the primary past focus was on achieving osseointegration, contemporary research emphasizes broadening the limits of dental implantology. Dental implants can now be loaded immediately after achieving required primary stability, even before osseointegration occurs. Osseointegration is feasible in compromised patients with conditions like diabetes or HIV. Advancements in medical care and pharmacotherapy may introduce new effects influencing bone healing and osseointegration. Furthermore, manufacturers are enhancing the range of available products through surface and shape modifications, with certain modifications, including laser treatments or coatings, showing improved outcomes and expedited osseointegration. CONCLUSION: Identified key influencing factors aid practitioners in achieving successful implant restorations. With this knowledge, practitioners can better anticipate treatment outcomes, considering all factors, including the patient, dental team, and implant itself.